Implementasi Peraturan Daerah Kota Padang Nomor 3 Tahun 2019 tentang Rencana Tata Ruang Wilayah dalam Pengembangan Sistem Permukiman - Putra, Lidra Syarif (Administratie: Jurnal Administrasi Publik, 2026)
This research is motivated by the importance of effective spatial planning management as a foundation to support sustainable development in the city of Padang, especially following the enactment of Regional Regulation Number 3 of 2019 concerning the Spatial Plan (RTRW). The main focus of this study is the evaluation of RTRW implementation in the development of settlement systems, which is a crucial aspect of urban planning. Using the policy implementation framework of Van Meter and Van Horn, which emphasizes six main indicators, this research aims to analyze the effectiveness level of policy implementation. The method used is descriptive qualitative, with data collected through in-depth interviews, documentation, and field observations at several locations where spatial planning violations have occurred. This approach enables a comprehensive understanding of the factors that influence both the success and obstacles in policy implementation. The research findings reveal that the implementation of Padang City’s RTRW regulation has not run optimally, due to limited competent human resources, weak coordination among related agencies, and low public awareness and participation regarding spatial planning regulations. This situation negatively impacts the development of settlement systems and the quality of the living environment in Padang. These findings underscore the need for capacity building of human resources, strengthening cross-sectoral coordination, and intensifying education and outreach to the public to ensure more effective RTRW implementation. With these measures, it is expected that well-organized and sustainable settlement development can be realized in Padang during the 2024-2025 period.